Role of TRPV1 channels of the dorsal periaqueductal gray in the modulation of nociception and open elevated plus maze-induced antinociception in mice - Mascarenhas, Diego Cardozo [UNESP]; Gomes, Karina Santos [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier B. V., 2015)
Recent findings have identified the presence of transient receptor potential vanilloid-1 (TRPV1) channels within the dorsal portion of the periaqueductal gray (dPAG), suggesting their involvement in the control of pain and environmentally-induced antinociception. Environmentally, antinociception may be achieved through the use of an open elevated plus maze (oEPM, an EPM with 4 open arms), a highly aversive environmental situation. Here, we investigated the role of these TRPV1 channels within the dPAG in the modulation of a tonic pain and in the oEPM-induced antinociception. Male Swiss mice, under the nociceptive effect of 2.5% formalin injected into the right hind paw, received intra-dPAG injections of the TRPV1 agonist (capsaicin: 0, 0.01, 0.1 or 1.0 nmol/0.2μL; Experiment 1) or antagonist (capsazepine: 0, 10 or 30nmol/0.2μL; Experiment 2) or combined injections of capsazepine (30nmol) and capsaicin (1.0nmol) (Experiment 3) and the time spent licking the formalin-injected paw was recorded. In Experiment 4, mice received intra-dPAG capsazepine (0 or 30nmol) and were exposed to the oEPM or to a control situation, an enclosed EPM (eEPM; an EPM with 4 enclosed arms). Results showed that while capsaicin (1 nmol) decreased the time spent licking the formalin-injected paw, capsazepine did not change nociceptive response. Capsazepine (30nmol) blocked pain inhibition induced by capsaicin and mildly attenuated the oEPM-induced antinociception. Our results revealed an important role of TRPV1 channels within the dPAG in the modulation of pain and in the phenomenon known as fear-induced antinociception in mice.
Keywords: Antinociception; Formalin test; Mice; Open elevated plus maze; Periaqueductal gray matter; Trpv1